(untitled) (Bioagro, 2021)
The cinchona tree (Cinchona officinalis), an emblematic species of Peru, has for many years been threatened with extinction. The objective of this study was to evaluate the influence of the type of mini-stake (apical and basal) and the absorption time of indole-butyric acid (0, 2, 6, and 10 minutes) on the clonal multiplication of the cinchona tree. The shoots were collected from trees of natural populations present in the Conila-Peru montane forest, at an altitude of 2800 m. The mini-cuttings, basal and apical, were treated with indole butyric acid at 2000 mg·L-1 and were left to rest for different times. The data were subjected to an analysis of variance and the means were compared with the Tukey test. After 60 days, it was found that the basal mini-cuttings presented a significantly higher rooting percentage (54.77 %) compared to the apical mini-cuttings (40.10 %), being also higher in survival (62.75 %) and size of roots (17.38 mm). The absorption times of 6 and 10 minutes turned out to be the most outstanding, while the control (0 minutes) turned out to be the lowest treatment. In conclusion, the basal mini-cuttings and the absorption times of 6 and 10 minutes turn out to be the most appropriate to guarantee the rooting of mini-cuttings of the cinchona tree.